2010
DOI: 10.1080/13607863.2010.501060
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory factor analysis of the Center for Epidemiologic Studies – Depression Scale in Black and White dementia caregivers

Abstract: Objectives In order to better understand if measurement problems underlie the inconsistent findings that exist regarding differences in depression levels between Black and White caregivers, this study examined the factor structure and invariance of the Center for Epidemiologic Studies-Depression scale (CES-D). Method A confirmatory factor analysis of the 20-item CES-D was performed on a sample of 167 Black and 214 White family caregivers of older adults with dementia from Los Angeles County. Results The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
(39 reference statements)
1
9
0
Order By: Relevance
“…The invariance of factor structure of the 12-item CES-D scale in this study is in line with CFA for the original 20-item CES-D scale in previous studies, which found the same factor model for Blacks (27), Black women (55, 56), and Black caregivers (57, 58). Torres used the NSAL data and showed that among Black men with Caribbean ancestral ties, CES-D scale scores were not associated with CIDI-based MDD or dysthymia (59).…”
Section: Discussionsupporting
confidence: 90%
“…The invariance of factor structure of the 12-item CES-D scale in this study is in line with CFA for the original 20-item CES-D scale in previous studies, which found the same factor model for Blacks (27), Black women (55, 56), and Black caregivers (57, 58). Torres used the NSAL data and showed that among Black men with Caribbean ancestral ties, CES-D scale scores were not associated with CIDI-based MDD or dysthymia (59).…”
Section: Discussionsupporting
confidence: 90%
“…Its development was based on Beck's four-factor model of depression, which includes positive affect, negative affect, somatic symptoms and retarded activity, and interpersonal difficulties. While many studies have documented this four-factor structure [ 12 ], some research suggests that these factors may vary across different groups [ 13 ], which raises concern about its generalizability.…”
Section: Introductionmentioning
confidence: 99%
“…Caregiver burden has been defined as “a multidimensional response to the negative appraisal and perceived stress resulting from taking care of an ill person” (Kim et al., , p. 846). High levels of depressive symptoms have been documented among caregivers of persons with dementia (CPD) and one third of these caregivers meet the diagnostic criteria for clinical depression (Cooper, Katona, Orrell, & Livingston, ; Fisher et al., ; Flynn Longmire & Knight, ; Schultz & Martire, ; Tremont, ). In addition, high levels of anxiety have been found in 10–35% of CPD (Cooper, Katona, Orrell, & Livingston, ; Cooper, Balamurali, & Livingston, ; Cooper, Balamurali, Selwood, & Livingston, ; Cooper et al., ).…”
mentioning
confidence: 99%